2002
DOI: 10.1523/jneurosci.22-20-08971.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Region and Leucine Zipper Transcription Factor MafK Is a New Nerve Growth Factor-Responsive Immediate Early Gene That Regulates Neurite Outgrowth

Abstract: We used serial analysis of gene expression to identify new NGF-responsive immediate early genes (IEGs) with potential roles in neuronal differentiation. Among those identified was MafK, a small Maf family basic region and leucine zipper transcriptional repressor and coactivator expressed in immature neurons. NGF treatment elevates the levels of both MafK transcripts and protein. In contrast, there is no effect on expression of the closely related MafG. Unlike many other NGF-responsive IEGs, MafK regulation sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 71 publications
3
31
0
Order By: Relevance
“…In extension of pioneer- ing large-scale studies that previously identified NGFresponsive genes (Lee et al 1995(Lee et al , 2005Mayumi et al 1998;Brown et al 1999;Angelastro et al 2000Angelastro et al , 2002Torocsik et al 2002), we show that expression of NGFresponsive genes is very time dependent. In particular the K-means clusters graph illustrates that timing of up-or down-regulation of a gene is a fundamental aspect of acquisition of the neuronal phenotype.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In extension of pioneer- ing large-scale studies that previously identified NGFresponsive genes (Lee et al 1995(Lee et al , 2005Mayumi et al 1998;Brown et al 1999;Angelastro et al 2000Angelastro et al , 2002Torocsik et al 2002), we show that expression of NGFresponsive genes is very time dependent. In particular the K-means clusters graph illustrates that timing of up-or down-regulation of a gene is a fundamental aspect of acquisition of the neuronal phenotype.…”
Section: Discussionsupporting
confidence: 70%
“…A number of different techniques to achieve this have been employed and range from targeted display, to expressed sequence tag analysis, serial analysis of gene expression (SAGE), and microarray analysis (Lee et al 1995(Lee et al , 2005Mayumi et al 1998;Brown et al 1999;Angelastro et al 2000Angelastro et al , 2002Torocsik et al 2002;Marek et al 2004). In particular, SAGE and microarray analysis have become prominent methods to pursue these goals.…”
mentioning
confidence: 99%
“…For example, neurotrophic signals up-regulate synthesis of lipids and their synthetic enzymes supporting axon outgrowth (Araki and Wurtman 1997). Transcription factors are now being identified that are both regulated by neurotrophins and required for axon outgrowth, for example, the immediate early gene MafK (Torocsik et al 2002). Even more interestingly, axon growth requires the transcription of genes specific for axon elongation.…”
Section: How Do Extracellular Signals Induce Axon Elongation?mentioning
confidence: 99%
“…Although RNAi has recently been shown to function in mammalian neurons (Gaudilliere et al, 2002;Krichevsky and Kosik, 2002;Torocsik et al, 2002), there are several specific problems that limit its usefulness in such cells. One is that the delivery procedure itself, which often uses lipid transfection reagents or electroporation, can induce neuronal damage and death and thus alter experimental outcome or interpretation.…”
Section: Introductionmentioning
confidence: 99%